Genetic Determinants of Antibacterial Resistance Among Nosocomial Escherichia coli Klebsiella spp., and Enterobacter spp. Isolates Collected in Russia within 2003-2007 - S. D. Pryamchuk; N. K. Fursova; I. V. Abaev; YU. N. Kovalev; N. A. Shishkova; E. I. Pecherskikh; O. V. Korobova; E. I. Astashkin; D. M. Pachkunov; A. N. Kruglov; D. V. Ivanov; S. V. Sidorenko; et al. (Антибиотики и Химиотерапия, 2020)
Nosocomial bacterial Isolates collected within 2003-2004 (n=411) and 2005-2007 (n=422) were highly resistant to cephalosporins III-IV and antibacterials of other groups (aminoglycosides, fluoroquinolons, chloramphenicol, and co-trimoxazole). Genes encoding TEM, SHV, CTX-M, OXA-2, and AmpC types of beta-lactamases (BLs) in the E.coli, Klebsiella spp., and Enterobacter spp. isolates were detected using polymerase chain reaction (PCR). Prevalent CTX-M-type BLs were detected in 85% of the E.coli, 87% of the Klebsiella spp., and 38% of the Enterobacter spp. isolates of the first strain collection and in 94% of the E.coli, 91% of the Klebsiella spp., and 38% of the Enterobacter spp. isolates of the second one. Genes belonging to three subtypes of blaCTX-M genes were identified: blaCTX-M-1 (228 blaCTX-M-15 and six blaCTX-M-3 of the first strain collection; 275 blaCTX-M-15, three blaCTX-M-3, and one blaCTX-M-22 of the second one), blaCTX-M-2 (one blaCTX_M_5 of the first strain collection and one blaCTX-M-2 of the second one), blaCTX-M-9 (17 blaCTX-M-14 and one blaCTX-M-9 of the first strain collection; seven blaCTX-M-14 and one blaCTX-M-9 of the second one). Three isolates of the first strain collection and one isolate of the second one carried two genes belonging to two different subtypes i. e. blaCTX-M-15 and blaCTX-M-14 simultaneously. The bacterial isolates had high levels of associative resistance to ciprofloxacin, co-trimoxazole, gentamicin, amikacin, and chloramphenicol associated with the resistance gene cassettes aadA1, aadA2, aadA5, aadB, aacA4, aac(6)Ib; dfrA1, dfrA5, dfrA12, dfrA17, cmlA1, ereA2, and catB8 in the class 1 integrons and the resistance gene cassettes dfrA1, sat1, and aadA1 in the class 2 integrons.